Unraveling the Novel Effect of Patchouli Alcohol Against the Antibiotic Resistance of Helicobacter pylori - Zhong, Yuanzun; Tang, Liyao; Deng, Qiuhua; Jing, Li; Zhang, Jiao; Zhang, Yao; Yu, Feng; Ou, Yijun; Guo, Shaoju; Huang, Bin; Cao, Hongying; Huang, Ping; et al. (Frontiers in Microbiology, 2021)
The long-term colonization of Helicobacter pylori (H. pylori) can cause various gastrointestinal diseases, and its high genetic variability makes it resistant to antibiotics and leads to the failure of clinical treatment. Intracellular survival also contributes to the drug resistance of H. pylori. Patchouli alcohol (PA) shows highly efficient activity against H. pylori in vitro and in vivo. And this study aims to explore whether PA can reduce the resistance of H. pylori and determine the underlying mechanism. Checkerboard and time–kill curve assay reveal that the combination of PA and clarithromycin (CLR) promoted the inhibition and bactericidal effect against H. pylori. The number of intracellular H. pylori increased with low dose CLR stimulation, but PA can effectively inhibit the invasion induced by CLR. Compared with antibiotics, PA remarkably eradicated the intracellular H. pylori, and this intracellular sterilized ability was further improved in combination with antibiotics (CLR and metronidazole). The expression of H. pylori efflux genes (hp0605, hp1327, and hp1489) was dose-dependently downregulated by PA. Digital droplet PCR indicated that the mutant of H. pylori gene A2143G can be inhibited by PA. Cellular uptake and transport assays showed that PA is rapidly absorbed, which promotes its activity against intracellular bacteria. Therefore, PA can act synergistically with CLR as a candidate treatment against the drug-resistant H. pylori.